From Eve to Dawn, A History of Women in the World, Volume IV : Revolutions and the Struggles for Justice in the 20th Century. - French, Marilyn, 1929-2009 (Feminist Press at CUNY, 2008)
From the author of The Women's Room, the best-selling novel that defined the issues that ignited the women's movement, comes a vibrant history of the political revolutions of the twentieth century, ending with a thoughtful investigation into feminist movements throughout the world and into the future.